2021
DOI: 10.1037/spy0000262
|View full text |Cite
|
Sign up to set email alerts
|

How team socialization processes relate to youth ice hockey players’ social identity strength and cohesion.

Abstract: How new members are integrated into a particular group environment—also known as organizational socialization processes—have been shown to be a powerful predictor of newcomer adjustment in the workplace. Yet, there is a scarcity of research on how sport teams manage the integration of new team members, and the consequences of different tactics. The current research evaluated how socialization processes are associated with youth athletes’ perceptions of their group environment. Across two time points, 202 compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Bruner et al (2015) found that teams and individuals that had higher perceptions of outcome interdependence reported greater identification with the team. Finally, mediation analysis supported that coachinitiated role communication tactics related to changes in social identity strength which, in turn, was associated with higher levels of task and social cohesion (Chamberlain et al, 2021).…”
Section: Group Level Variables Associated With the Performance Hypoth...mentioning
confidence: 79%
See 2 more Smart Citations
“…Bruner et al (2015) found that teams and individuals that had higher perceptions of outcome interdependence reported greater identification with the team. Finally, mediation analysis supported that coachinitiated role communication tactics related to changes in social identity strength which, in turn, was associated with higher levels of task and social cohesion (Chamberlain et al, 2021).…”
Section: Group Level Variables Associated With the Performance Hypoth...mentioning
confidence: 79%
“…Teamwork, Group Dynamics, and Cohesion. Nine studies provided evidence to support the positive relationship between social identity and teamwork, group dynamics, or cohesion (Bruner et al, 2015(Bruner et al, , 2021Campo et al, 2022;Chamberlain et al, 2021;DeBacker et al, 2011;DeBacker et al, 2022;Fransen et al, 2020;Worley et al, 2020). Both Worley et al (2020) and DeBacker and colleagues (2022) found a significant relationship between social identity and cohesion (β = .92 and r = .69, respectively).…”
Section: Group Level Variables Associated With the Performance Hypoth...mentioning
confidence: 97%
See 1 more Smart Citation
“…Research shows that sports can promote the establishment of young people’s values. Being constrained by various rules in sports participation can also promote the formation of social behavior norms, which is conducive to the formation of social and cultural values ( Chamberlain et al, 2021 ). The traditional form of school sports organization no longer promotes the socialization of young people.…”
Section: Discussionmentioning
confidence: 99%
“…De esta forma, estas interacciones que se producen dentro de un equipo deportivo se inician desde los primeros días de temporada (Carron & Eys, 2012;Coleman et al, 2021), considerándose a este inicio como un proceso fundamental para confeccionar un correcto funcionamiento colectivo (Benson & Eys, 2017;Chamberlain et al, 2021) y para generar un sentimiento de persistencia entre los jugadores que forman parte del equipo (Chamberlain et al, 2021;Schwartz, 1973). Para relacionar la cohesión grupal con la persistencia en el equipo, existen estudios centrados en la adherencia deportiva.…”
Section: Introductionunclassified